2020
DOI: 10.3390/children7070077
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Garments in Individuals with Autism and Severe Proprioceptive Dysfunction: A Retrospective Exploratory Case Series

Abstract: (1) Background: Compression garments (CGs) are an adjuvant treatment for generalized joint hypermobility (GJH), including the Ehlers–Danlos syndrome/hypermobility types. The effects of CGs are likely to be related to better proprioceptive control. We aimed to explore the use of CGs in individuals with autism and severe proprioceptive dysfunction (SPD), including individuals with GJH, to control posture and challenging behaviors. (2) Methods: We retrospectively described 14 patients with autism and SPD, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
(105 reference statements)
1
4
0
Order By: Relevance
“…Previous work suggested that CGs may improve proprioception in patients with EDS and that this may lead to decreased pain [ 12 ]. In line with this, several studies showed improved postural control in patients wearing CGs [ 22 , 38 , 39 ]. In our study, we did not directly test proprioception, but we used the Berg Balance Scale to assess postural control.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous work suggested that CGs may improve proprioception in patients with EDS and that this may lead to decreased pain [ 12 ]. In line with this, several studies showed improved postural control in patients wearing CGs [ 22 , 38 , 39 ]. In our study, we did not directly test proprioception, but we used the Berg Balance Scale to assess postural control.…”
Section: Discussionsupporting
confidence: 54%
“…They are usually selected to cover specific anatomical regions that may benefit from the CGs, such as the ankles, knees, hips, or hands. It is thought that CGs may be of benefit to patients with EDS by improving proprioception [ 12 , 22 ]. It was suggested that this may involve ‘filtering’ effects, where the CGs reduce the transmission of irrelevant sensory information so that proprioception is improved [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these techniques was successful in eliminating the target behavior. Guinchat et al (2020) conducted a study with 14 young patients with severe autism and proprioceptive impairment. Half of them had JHM and the majority had challenging behaviors.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Literature shows mixed results for sensory interventions, and research on various sensory garments as a primary support for sensory processing is limited. Compression garments are one type of deep pressure intervention that may help regulate the sensory system through pressure applied to the body [ 19 , 20 ]. As these garments distribute pressure evenly on the body compared to weighted vests which localize pressure to the shoulders, they may promote increased body awareness and focus.…”
Section: Introductionmentioning
confidence: 99%